Racial and Ethnic Differences in Short- and Long-Term Mortality by Stroke Type. (14th June 2022) - Tarko, Laura; Costa, Lauren; Galloway, Ashley; Ho, Yuk-Lam; Gagnon, David; Lioutas, Vasileios; Seshadri, Sudha; Cho, Kelly; Wilson, Peter; Aparicio, Hugo J.
Abstract : Background and Objectives: Racial and ethnic disparities in stroke outcomes exist, but differences by stroke type are less understood. We studied the association of race and ethnicity with stroke mortality, by stroke type, in a national sample of hospitalized patients in the Veterans Health Administration. Methods: A retrospective observational study was performed including non-Hispanic White, non-Hispanic Black, and Hispanic patients with a first hospitalization for stroke between 2002 and 2012. Stroke was determined using ICD-9 codes and date of death was obtained from the National Death Index. For each of acute ischemic stroke (AIS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH), we constructed a piecewise multivariable model for all-cause mortality, using follow-up intervals of ≤30 days, 31–90 days, 91 days to 1 year, and >1 year. Results: Among 37, 790 patients with stroke (89% AIS, 9% ICH, 2% SAH), 25, 492 (67%) were non-Hispanic White, 9, 752 (26%) were non-Hispanic Black, and 2, 546 (7%) were Hispanic. The cohort was predominantly male (98%). Compared with White patients, Black patients experienced better 30-day survival after AIS (hazard ratio [HR] 0.80, 95% CI 0.73–0.88; 1.4% risk difference) and worse 30-day survival after ICH (HR 1.24, 95% CI 1.06–1.44; 3.2% risk difference). Hispanic patients experienced reduced risk for >1-year mortality after AIS (HR 0.87, 95% CI 0.80–0.94), but had greater risk of 30-day mortality after SAH compared with White patients (HR 1.61, 95% CI 1.03–2.52; 10.3% risk difference). Discussion: Among US Veterans, absolute risk of 30-day mortality after ICH was 3.2% higher for Black patients and after SAH was 10.3% higher for Hispanic patients compared with White patients. These findings underscore the importance of investigating stroke outcomes by stroke type to better understand the factors driving observed racial and ethnic disparities.